Althusser and Wittgenstein : Ideology and Therapeutic Analysis of Language - Karczmarczyk, Pedro (Rethinking Marxism.)
This paper focuses on the convergence of the positions of Wittgenstein and Althusser. The discussion on the political implications of Wittgenstein's thought has revolved around the possibility (or impossibility) of taking his ideas as standpoints for a critical view of the social dimension, its legitimacy, reach, and strength. However, translating Wittgenstein's thoughts into an Althusserian materialistic position leads to an understanding of the critiques within the former's work that does not hinge on their warranty as a point of view but on the effects of deconstructing the philosophical discourse, which seeks to unify and to arrange hierarchically the evidences (certainties) constitutive of the different language games in which the social is displayed. The paper concludes with some remarks on the distinction-borrowed from Wittgenstein and Althusser-between philosophy as an ideological-theoretical practice and as a critical-theoretical practice.